The Monetary Value of Saving a High-Risk Youth - Cohen, Mark A. (Journal of quantitative criminology, 1998)
Programs targeted at high-risk youth are designed to prevent high-school dropout, crime, drug abuse, and other forms of delinquency. Even if shown to be successful in reducing one or more social ill, a key policy question is whether the cost to society from that intervention program exceeds its benefits. Although the costs of intervention programs are often available, the benefits are more illusive. This paper provides estimates of the potential benefits from “saving” a high-risk youth, by estimating the lifetime costs associated with the typical career criminal, drug abuser, and high-school dropout. In the absence of controlled experimental data on the number of career criminals averted, one can ask the reverse question—How many career criminals must be prevented before the program “pays for itself?” Based on a 2% discount rate, the typical career criminal causes $1.3–$1.5 million in external costs; a heavy drug user, $370,000 to $970,000; and a high-school dropout, $243,000 to $388,000. Eliminating duplication between crimes committed by individuals who are both heavy drug users and career criminals results in an overall estimate of the “monetary value of saving a high-risk youth” of $1.7 to $2.3 million.